2023
DOI: 10.1371/journal.pone.0271388
|View full text |Cite
|
Sign up to set email alerts
|

LPF-Defense: 3D adversarial defense based on frequency analysis

Abstract: The 3D point clouds are increasingly being used in various application including safety-critical fields. It has recently been demonstrated that deep neural networks can successfully process 3D point clouds. However, these deep networks can be misclassified via 3D adversarial attacks intentionality designed to perturb some point cloud’s features. These misclassifications may be due to the network’s overreliance on features with unnecessary information in training sets. As such, identifying the features used by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The approach for target selection will depend on the specific objectives in a given scenario. For example, Wu et al [98] and Naderi et al [99] have utilized the latter approach, while Ma et al [64] have explored both strategies in their work.…”
Section: Target Typementioning
confidence: 99%
See 1 more Smart Citation
“…The approach for target selection will depend on the specific objectives in a given scenario. For example, Wu et al [98] and Naderi et al [99] have utilized the latter approach, while Ma et al [64] have explored both strategies in their work.…”
Section: Target Typementioning
confidence: 99%
“…This is the author's version which has not been fully edited and content may change prior to final publication. Citation information: DOI 10.1109/ACCESS.2023.3345000 c: Low Pass Frequency-Defense (LPF-Defense)In LPF-Defense[99], deep models are trained with the lowfrequency version of the original point clouds. More specifically, using the Spherical Harmonic Transform (SHT)[114], original point clouds are transformed from the spatial to the frequency domain.…”
mentioning
confidence: 99%
“…Following this, a nonlinear binary classifier CRT : C → {0, 1} is trained to discern whether the point cloud has been polluted by an Considering that current backdoor defense methods for 3D point clouds are very limited, we additionally introduce two adversarial defense algorithms oriented toward 3D point clouds in Tab.V. [40] observed that the attack pattern typically resides in the high-frequency portion of the spherical harmonic domain and consequently designed a low-pass filter (LPF) to eliminate the attack. [41] proposed a denoise and upsampling(DUP) method to tackle the attack.…”
Section: ) Resistance To Data Augmentationmentioning
confidence: 99%